(untitled) (The Peerian Journal, 2024)
Water is a prime commodity; however, it faces several challenges in its contamination by the emerging pollutants which include pharmaceuticals, industrial chemicals, and personal care products. These find their ways into the water either through sewage, agriculture, industrial discharge, or poor waste disposal. Most of these pollutants cannot be removed easily by the conventional methods due to their unstable nature. Some dispersal pathways involve biodegradation, chemical degradation, sedimentation, and evaporation. Advanced technologies like bioremediation, nanofiltration, and filtration techniques have come forward to deal with these pollutants. Understanding of these pollutants and their removal methods will help in improving the water quality and preserving the environment